Gondolatok az európai szerződési jog új irányairól - Béky, Ágnes Enikő (Debreceni Jogi Műhely, 2008)
On the field of contract law the European Union started a wide legislative effect at the end of the 20th Century. Despite of the originally economic and public legal goals of the Communities recently the competence of the EC institutions conquest a major field in the area of private law. To ensure the fast and non-problematic acceptance of these directives concerning to contract law EC chose two important solutions. Most of the directives focus on the neglected area of the so-called atypical contracts (hawk contracts, e-commerce contracts, leasing contracts, factoring contracts, etc.). As these contractual forms were born in the hands of business actors, most of the European civil codes do not deal with them in an explicit way. As a gap of law this area is the best approach to create unified legal institutions in all Member States’ legislation. The other relevant factor is the law of consumer protection. This is not only a fashionable topic in Europe but a rather underdeveloped issue in – especially – the new Member States. Almost all legal institutions in the EC directives in connection with contract law contain a strong link to protecting customers. As and indirect effect, these new institutions (such as consumer’s right to withdrawal) found their ways in the national codes to be flagships applicable for all consumer contracts. This essay contains thoughts about these relevant changes in approaching contract law from the rather unique EC perspective.